Aligning and observing the liquid crystal director in 3D using small magnetic fields and a wedge-cell - Gulati, Lovish; Sánchez-Somolinos, Carlos; Gießelmann, Frank; Fischer, Peer (Advanced functional materials, 2025)
The mechanical and optical properties of liquid crystalline materials are largely dependent on the director profile. More complex soft robotic functions and programmed optical properties require spatially varying director profiles, ideally in 3D. However, it is challenging to achieve arbitrary director orientation with most established alignment techniques, as one needs to overcome surface interactions, use high electric or magnetic field strengths and temperatures. Another experimental difficulty is that there is a lack of suitable techniques that can be used to characterize the director in 3D. Here, this study first shows that the addition of 5CB to reactive mesogens permits cross-linked liquid crystalline materials to be fabricated with a spatially varying 3D director profile using weak magnetic fields (0.13 T). This study also shows, how these can be characterized with an optical technique that uses a wedge cell to visualize the programmed 3D director profile. Interestingly, the method also permits the real-time observation of the director. This work shows that it is possible to precisely control the director in 3D with low magnetic fields and that the dynamics can be directly observed, which facilitates potential applications of soft liquid crystalline (LC) gels and potentially also elastomers.
Online veröffentlicht: 9. Dezember 2024
Gesehen am 29.10.2025